Follow-Up to Case Study: Neurofeedback as a First Choice Treatment in an ADHD and Comorbidities - Paes de Barros França, F (KnE Life Sciences, 2018)
The purpose of this case study is to present the evolution in the neurofeedback treatment of a 7-years-old boy with ADHD and comorbidities – OCD, Anxiety and Aggression. The main complaint of parents and school was the lack of control of his impulses, beating his classmates, not sitting quietly in the classroom, disrupting classmates, biting fingernails and toes compulsively – getting hurt. He was asked to withdraw from the previous school and, the parents saw neurofeedback as an alternative non-drug treatment, since the psychiatrist suggested an antidepressant. Brain training by neurofeedback occurred twice a week, in a total of 70 sessions, where the brain areas with the greatest impairment were trained. With only two months of treatment, the boy’s aggressiveness was no longer a problem. At the end of the treatment, the functional impairments were better, validated by mean evolution evaluations. The patient was released, with a high approval rating from parents and school, since their symptoms disappeared. After 1 year and 9 months of the end of treatment at the age of 9, a new assessment was performed to see if the gains remained. The results showed that through Neurofeedback training the brain had the ability to normalize his electrical activity and maintain the gain over time. Keywords: ADHD, neurofeedback, rehabilitation